Menjaga Daya Tahan Tubuh dengan Olahraga Saat Pandemi Corona COVID-19 - Furkan, Furkan; Rusdin, Rusdin; Shandi, Shutan Arie (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Since the entry of Covid-19 in Indonesia, people have been asked to stay at home and do everything from home. While at home, maybe many people find it difficult to maintain their health because they cannot exercise outside the home as usual or they are lazing around too much at home. "When WFH (work from home) is like this, because our only choice is to exercise at home. "Exercise can increase the immune system and improve mood because you are constantly at home," said Mario. At least 150 minutes per week, he added, 30 to 60 minutes per session for 3-4 days a week. Routines are key in exercising from home during this pandemic. it will be very easy for people to fall into a relentless, lifestyles. "For that, it is necessary to create a daily routine in which physical exercise is one of the things that must be done every day. Exercising every day can provide a therapeutic feeling and bring life back to normal.